The Gospels and Acts - Levine, Amy-Jill (The Oxford handbook of New Testament, gender, and sexuality, 2019)
The Gospels and Acts do not present a single view of either gender or sexuality; inconsistencies appear both within and among this collection. Yet despite these differences, there is a common baseline regarding sexuality, masculinity, and femininity. Consequently, this chapter begins from that baseline and then moves to the several distinct chords and notes struck by each text. The analysis surveys a broad range of topics including celibacy and singleness, marriage and divorce, lust, masturbation, adultery, incest, prostitution, and gender roles, as well as investigation of specific themes in each of the Gospels and Acts.